Find the value for the above summation:
Providing that 'x' is an integer and the summation
implies the sum of all the values created by the function (inputting the variables) for integers between 'x' and a value 'n' including 'x' and 'n' .
E.G.:
=[2(1)+1]+[2(2)+1]+[2(3)+1]=3+5+7=15
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I f w e m a k e S 1 = f ( x ) , t h e n x S 1 2 = S 1 H e n c e : S 1 2 − x S 1 = 0 ; S 1 ( S 1 − x ) = 0 [ a n d w e a s s u m e S 1 = 0 ( a s u n l e s s x = 0 i t m u s t h a v e v a l u e ) ] S 1 = x . N o w w e n e e d t o f i n d a g e n e r a l f o r m u l a f o r x ∑ n f ( x ) w h e r e ′ n ′ i s j u s t a n i n t e g e r g r e a t e r t h a n x . A s f ( x ) = x , x ∑ n f ( x ) = x + ( x + 1 ) + ( x + 2 ) . . . + n . w e c a n s a y x ∑ n f ( x ) = ( n − 1 ) x + 2 1 ( n − x ) ( n − x + 1 ) ; x ∑ n f ( x ) = n x − x + 2 1 n 2 + n − 2 n x + x 2 − x ; T h i s s i m p l i f i e s t o : x ∑ n f ( x ) = 2 x 2 − 3 x + n 2 + n N o w w e m u s t t r y t o f i n d ′ x ′ : I f g ( x ) = x + x + x + x + x + x + x . . . w e c a n s a y t h a t S 2 2 − x = S 2 ; T h i s c a n b e s o l v e d ( a s a n y q u a d r a t i c ) t o g i v e : S = 2 1 ± 1 + 4 x . W e a r e t o l d t h a t g ( x ) = ∣ x ∣ h e n c e 2 1 ± 1 + 4 x = ∣ x ∣ T h i s c a n b e s o l v e d i n t w o u n i q u e w a y s ( d e p e n d i n g o n s i g n s ) , s i m p l y b y r e a r r a n g e m e n t : O n e w a y y i e l d s a s i n g l e r e s u l t x = 0 , t h e o t h e r y i e l d s t w o : x = 0 a n d x = 2 . W e k n o w x = 0 f r o m t h e q u e s t i o n , h e n c e f o r t h i s s o l u t i o n x = 2 . T h e r e f o r e 5 x ∑ ( 5 x ) 2 f ( x ) c a n b e c h a n g e d t o 1 0 ∑ 1 0 0 f ( x ) b y i n p u t o f x = 2 . W e k n o w t h a t t h e s u m m a t i o n e q u a t i o n i s : 2 x 2 − 3 x + n 2 + n { o r 2 2 x 2 − 3 x + x 4 } . H e n c e t o f i n d t h e v a l u e o f t h e s u m m a t i o n : 2 2 ( 1 0 0 ) 2 − 3 ( 1 0 0 ) + ( 1 0 0 ) 4 − 2 2 ( 9 ) 2 − 3 ( 9 ) + ( 9 ) 4 = 5 0 0 0 9 8 5 0 − 3 3 4 8 = 5 0 0 0 6 5 0 2 .
P.S. Apologies for the horrendous layout of this solution. :/